Experience with the use of intraoperative continuous nerve monitoring in video‐assisted neck surgery and external cervical incisions. Issue 2 (26th February 2021) - Noda, Takuya; Ishisaka, Tomo; Okano, Keiichiro; Kobayashi, Yoshiaki; Shimode, Yuzo; Tsuji, Hiroyuki
Abstract: Objectives: Recurrent laryngeal nerve (RLN) injury is one of the severe complications in thyroid surgery. Therefore, intraoperative nerve monitoring (IONM) has been widely used to identify the RLN and confirm its integrity. Recently, the usefulness of continuous IONM (CIONM) with automatic, periodic stimulation to the vagus nerve during thyroid surgery was reported. This study aimed to report our experience with minimally invasive video‐assisted endoscopic endocrine neck surgery (VANS), during which, CIONM was successfully applied for the first time. Methods: Consecutive patients who underwent thyroid surgery with CIONM, performed in our department using either external neck incision surgery or VANS between July 2017 and June 2019, were retrospectively analyzed. Results: A total of 22 patients who underwent thyroid surgery with neck incision (14 cases; 7 men and 7 women; age, 21‐75 years [mean, 52 years]) or VANS (8 cases; 8 women, age, 20‐61 years [mean, 41 years]) were enrolled in this study. The addition of CIONM in VANS prolonged the operation's duration by approximately 30 minutes as the endoscopic surgery was technically more difficult. No intra‐ and postoperative incidence of transient or permanent RLN palsy was observed in any patient, except for three patients who underwent external neck incision surgery in whom combined resection was unavoidable due to tumor invasion of the RLN. Conclusion: We reported the first successful application of CIONM during thyroidectomy using VANS. Future clinical trials should clarify the benefits of CIONM when compared to intermittent IONM in VANS. Level of Evidence: 5.